Risk Overgeneralization in Times of a Contagious Disease Threat - Lee, Spike W. S.; Huang, Julie Y.; Schwarz, Norbert (Frontiers in Psychology, 2020)
People’s assessment of risks is swayed by their current feelings. COVID-19 invokes powerful feelings because it is (i) a salient, enormous threat, (ii) unfamiliar, and (iii) intertwined with xenophobia. These three factors are known to exert predictable influence on people’s risk overgeneralization, policy preference, and sociopolitical attitudes. We provide a succinct, illustrative review of empirical work on these dynamics in times of a disease outbreak (e.g., the 2009 H1N1 swine flu, the 2014 Ebola). Theoretical and applied implications for the present COVID-19 pandemic include the value of salience in motivating public opinion change, the importance of reducing unfamiliarity for curbing risk-averse tendencies, and the need for policies that guard against xenophobia-driven racism in collaborative efforts.